2019
DOI: 10.1002/lary.28310
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for auricular hematoma and recurrence after drainage

Abstract: Objectives/Hypothesis To review an institutional experience with auricular hematoma across all clinical settings including the emergency department (ED) and outpatient clinics at an urban tertiary care academic hospital, characterize practice patterns across setting and specialty, and assess for factors predictive of treatment success. Methods Patients presenting to the ED, admitted to an inpatient ward, or seen in the outpatient setting between 2000 and 2017 with a diagnosis of auricular hematoma were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Dalal et al conducted a study which included 87 patients with pinna haematoma. Factors linked to a reduced recurrence rate included initial treatment by ENT doctors and the application of bolster dressing 7. In 2017, Vijendren and colleagues conducted a retrospective observational study—MaPHaeS—looking at the management options of pinna haematoma and their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Dalal et al conducted a study which included 87 patients with pinna haematoma. Factors linked to a reduced recurrence rate included initial treatment by ENT doctors and the application of bolster dressing 7. In 2017, Vijendren and colleagues conducted a retrospective observational study—MaPHaeS—looking at the management options of pinna haematoma and their effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Drainage is performed via a surgical incision on the helical rim or margin of the most prominent area followed by removal or irrigation of the extravasated blood and fluids. To prevent recurrence, a drain, sutures, or adequate compression using a splint or bolster should be applied for several days to inhibit dead space formation [2][3][4][5][6][7][8][9]. Recently, steroid or OK-432 application has also been considered as an option [1,[10][11][12]] and a previous report demonstrated good results with fibrin glue hemostatic material [13].…”
Section: Discussionmentioning
confidence: 99%
“…If not treated properly, it can cause a deformity known as 'cauliflower ear' or 'wrestler's ear.' There is no consensus on the best treatment method, and various surgical techniques have been described [1][2][3][4][5][6][7][8]. We report a case of othematoma that was inappropriately treated.…”
Section: Introductionmentioning
confidence: 95%
“…2 However, a 17-year study showed that recurrence rates were as high as 77% and that even with proper drainage and bolstering recurrence rates were 14%. 3 Hematomas prevent diffusion to the cartilage, leading to chondritis and potentially the development of cauliflower ear. 1 With this current understanding of the pathophysiology of the sequalae of auricular hematomas, we sought to find a novel surgical approach to manage these recalcitrant cases to prevent this cosmetic deformity.…”
Section: Introductionmentioning
confidence: 99%
“…Various treatment options have been described, with most involving extracting the hematoma and providing some form of pressure to the area 2 . However, a 17‐year study showed that recurrence rates were as high as 77% and that even with proper drainage and bolstering recurrence rates were 14% 3 . Hematomas prevent diffusion to the cartilage, leading to chondritis and potentially the development of cauliflower ear 1 .…”
Section: Introductionmentioning
confidence: 99%